Implementasi CIPP untuk Evaluasi Program Pelayanan Kesehatan Lingkungan di Kota Surabaya - Adella Putri Auliah Hapsari; Pratiwi Hermiyanti; Khambali .; Setiawan .; Nurifa Handayani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Environmental Health Services (EHS) are one of the programs of the Pegirian Public Health Center that has not met the Public Health Center Performance Assessment (HCPA) targets from counseling activities, environmental health inspections, and environmental health interventions. Research is needed with the aim of evaluating the EHS's impact on reducing Environmental-Based Disease (EBD) at the Pegirian Public Health Center in Surabaya City. This research is descriptive using a qualitative approach. The evaluation used the Context, Input, Process, Product (CIPP) method, then analyzed using Strength, Weakness, Opportunities, Threats (SWOT). The results of the study evaluated the context of the EHS program was in the good category, while the input, process and product evaluations were in the sufficient category. Additionally, patient/client visits for EBD still fluctuating since 2017-2022. Recommendations for strategies that the Pegirian Public Health Center can undertake in the EHS program include coordinating with sub-health centers (Pustu) and local area cadre to socialize the benefits of the EHS program, so that the community is willing and able to utilize the program and experience a reduction in EBD.Keywords: environmental health service; environmental-based disease; SWOT